1999
DOI: 10.1080/0267152990140207
|View full text |Cite
|
Sign up to set email alerts
|

Primary teaching as a career choice: the views of male andfemale sixth‐form students

Abstract: This paper reports the findings of a study which examined the factors influencing the choice of primary teaching as a career option among A-level students and how these factors differ between males and females. The views of males were of particular importance given the current disquiet in relation to recent trends in the recruitment of males as primary-school teachers. The paper reports that primary teaching is highly regarded as a career by all sixthformers, in that it is seen as performing a moral service to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
2
11
1
Order By: Relevance
“…Unlike previous findings in western countries (e.g. Johnston et al, 1999), but similar to those in China Mainland and Taiwan (see Lo, 1999;Fwu & Wang, 2002), teachers in Hong Kong were not seen as lacking in salary and social status. In addition, Lai et al (2000) also found out the interest in teaching was related to gender, academic results and streams of study.…”
Section: Introductioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Unlike previous findings in western countries (e.g. Johnston et al, 1999), but similar to those in China Mainland and Taiwan (see Lo, 1999;Fwu & Wang, 2002), teachers in Hong Kong were not seen as lacking in salary and social status. In addition, Lai et al (2000) also found out the interest in teaching was related to gender, academic results and streams of study.…”
Section: Introductioncontrasting
confidence: 78%
“…In terms of recruitment, the teaching profession fails to attract bright young people (Murnane et al, 1991;Kyriacou & Coulthard, 2000) and there is an underrepresentation of both qualified minority teachers (Newby et al, 1995) and males in the primary school teaching force (Johnston et al, 1999). The problem is also structural as a number of school subjects are constantly short of teachers with the required subject specialism, resulting in a high percentage of 'out-of-field' teaching (Coulthard & Kyriacou, 2002;Ingersoll, 2003).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…likes working with people, including children)". Indeed, looking at individual reasons for wanting to teach from recent studies, intrinsic or altruistic reasons were most frequently give by teachers, for example wanting to work with children (Johnston, McKeown and McEwen, 1999a, Moran et al, 2001, Smithers and Robinson, 2001, Thornton and Reid, 2001, Thornton, Bricheno and Reid, 2002, perceived job satisfaction (Johnston, McKeown and McEwen, 1999b, Thornton and Reid, 2001, Thornton, Bricheno and Reid, 2002, enjoyment of subject (Kyriacou and Benmansour, 1999) and positive experiences of teaching in the past (Hammond, 2002). The only extrinsic reason that emerged from any of the studies as the most cited reason to enter into teaching was "long holidays" Coulthard, 2000, Rawlinson et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%